An evaluation of the application of the courseware “Learn To Speak English Deluxe 10” in language lab for the first year non-major of English students at Hanoi University of Business and Technology - Phùng, Thị Như Trang (University of Languages and International Studies, 2017)
M.A Thesis English Teaching Methodology -- University of Languages and International studies. Vietnam National University, Hanoi, 2015